PENGARUH PENERAPAN METODE INKUIRI UNTUK PENGUASAAN KONSEP PADA PEMBELAJARAN PAK JARAK JAUH - Fernando Christofer; Wahyu Irawati (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2022)
Concepts comprehension is one of the important results for students. Low concept comprehension will make students get difficulty in problem-solving. The inquiry method is a means to improve 'students' conceptual understanding. The purpose of writing this practicum paper is to determine the efforts of improving 11th-grade 'students' conceptual understanding through the inquiry method in the distance learning context. The research using a descriptive qualitative method. It discusses five focuses of study, namely 'students' concept understanding in the learning process, the impact of inquiry methods in learning, the role of inquiry methods in improving students' conceptual understanding in distance learning, data analysis of 'students' with low understanding, and data analysis of increasing students' conceptual understanding through inquiry method. The research concluded that the inquiry method has succeeded-' in improving 11th-grade students’' conceptual understanding of distance learning. This success is supported by adequate technology advancements for teachers and students. The application of inquiry methods in improving students' conceptual understanding must be applied by Christian education purposes. Further research is suggested to analyze the effectiveness and success of inquiry method application by innovating strategies, media, or learning evaluation to improve the learning outcomes of students' conceptual understanding in the distance learning system.